INOVASI PENYIARAN MELALUI RRI PLAYGO DI KABUPATEN BENGKALIS - Febri Yuliani; Adianto; Sri Mawarti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Rapidly developing digitalization has changed world civilization, including information media. An easily accessible internet network makes people make various new breakthroughs as an alternative to using online media to obtain various information quickly. This study aims to describe in depth and comprehensively about broadcasting innovation through the RRI play go application as well as the supporting and inhibiting factors for broadcasting innovation through the RRI Play go application in Bengkalis Regency. This study uses a descriptive qualitative design, in which research data is collected through primary and secondary data through interviews of individual officials involved in the production or operational process of RRI Play go and several users of the RRI play go application. The results of the research look at the power of broadcast content in serving the public in Bengkalis Regency. Broadcasting innovation using the RRI Play go application is parallel to other media, so RRI is updating the system that compresses RRI play go, to widen the network so that socialization and mutual cooperation are carried out.